PERAN TEKNOLOGI INFORMASI DALAM PENGENTASAN KEMISKINAN DI INDONESIA - Syahriar, Rizky Qinthara; syahriar, ary (Badan Pengkajian dan Penerapan Teknologi, 2006)
A preliminary research on the roles of information can communication technology for poverty alleviation has been done. The research based on analysis of secondary data on ICT access and poverty data during the year 200-2006. It was found that there exist paradoxes where ICT infrastructure mainly concentrated in the capital city and other big cities but poverty mainly concentrated in rural area. These have created complex problem to solve poverty by using ICT. This paper is trying to introduce the roles of ICT and its solution in helping to reduce poverty in Indonesia.